Channeling Multiliteracies in Digital Era: A Case Study of EFL Student-Made Video Project in Vocational High School - Nadzifa Nur Fadila; Sri Setyarini; Gin Gin Gustine (Yayasan Visi Intan Permata, 2021)
The rapid growth of technology and the new demand of workforce in 21st century have intrigued the research to explore multiliteracies in EFL vocational high school through student-made video project. The skills to process information from mass media and operate in a digitized field are deemed to be necessary for vocational high school students. Student-made video project can be considered as an alternative in training students to enhance their multiliteracies skill, which will be explored in this research. Through a case study design, the integration process and salient modes of multiliteracies are captured. Involving a teacher and students of a vocational high school, the findings revealed that the student-made video project are conducted through four main stages, namely experiencing, conceptualizing, analyzing, and applying. The modes of multiliteracies appeared more frequent are visual representation, audio representation, and oral language in the form of video visual, audio of the video, script writing, and classroom discussion.